When your child is your cellmate: The ‘maternal pains of imprisonment’ in a Belgian prison nursery - Nuytiens, An (Criminology & criminal justice, 2022)
The experience of imprisonment is different for women and men: women suffer more, and they also suffer in more distinctive ways. For mothers in prison, the major pains of imprisonment are related to their motherhood status; the so-called maternal pains of imprisonment. Studies on those who have experienced motherhood in prison focus primarily on female prisoners who have been separated from their children. We explored whether women who cohabit with their child(ren) in prison also experience maternal pains of imprisonment, and how these pains are shaped. We draw upon the results of two small-scale qualitative studies conducted in a prison nursery in Belgium. Interviews with cohabiting mothers in this nursery revealed that although the mothers recognized several advantages of cohabitation, they also experienced maternal pains of imprisonment. These pains were related to witnessing and worrying about their child’s pains of imprisonment; the restriction of maternal autonomy; the overwhelming responsibility for their child; and for women with long-term sentences, worrying about the inevitable separation from their child.